Comparison of the Accuracy of Intraoperative Hemoglobin Measurement between Estimated Blood Loss and Point-of-Care Testing with Hematology Analyzer - Soenarto, Ratna Farida; Nugroho, Alfan Mahdi; Fahmy, Ahmad Faishal (Perdatin Pusat, 2015)
Measurement of Estimated Blood Loss (EBL) based on the Allowable Blood Loss (ABL) formula with certain hemoglobin target is often used to guide intraoperative transfusion. Point of Care Testing (POCT) offers easier way to measure haemoglobin. This study aimed to compare the accuracy of the intraoperative hemoglobin measurement between EBL and POCT with Hematology Analyzer in the laboratory as the golden standard. This study used a Bland-Altman test on intraoperative hemoglobin measurement in 43 patients undergoing elective surgery, which were expected require blood transfusion in the Operating Theater of Cipto Mangunkusumo Hospital from December 2014 until March 2015. When EBL had reached ABL with Hb level target 7 g/dL before transfusion was given, blood was drawn for Hb measurement with Sysmex XE-2100® as Hematology Analyzer and HemoCue® Hb 201+ as POCT. Bland-Altman analysis of Hb EBL (7 g/dL) to Hb Hematology Analyzer with interval considered as accurate for Hb 7 g/dL was -1 to 1, revealed wide limits of agreement (-2.267 to 2.467). Bland-Altman analysis of Hb POCT to Hb Hematology Analyzer revealed narrow limits of agreement (-0418 to 0372). There was a significant difference in the accuracy of intraoperative hemoglobin measurement by EBL compared to Hematology Analyzer. Additionally, the measurement by POCT device had good accuracy.